EVALUATING THE WORLD DIGITAL LIBRARY: A DIGITAL FRAMEWORK FOR GLOBAL CULTURAL PRESERVATION - Akhoon, Irfan ul Haq; Khan, Mashood Yousuf (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The rapid advancements in Information and Communication Technology (ICT), particularly the expansion of the World Wide Web (WWW), have led to a significant rise in digital library projects, especially in developed nations. These initiatives have revolutionized the way information is created, retrieved, disseminated, and utilized globally. In this context, the World Digital Library (WDL) emerges as a free, multilingual digital platform that preserves and provides access to diverse cultural and historical materials worldwide. This study critically examines the content and structure of WDL, focusing on country-wise contributions, time period coverage, subject classification, item types, language diversity, and institutional participation. The analysis provides insights into the composition and accessibility of WDL’s vast collection, which includes manuscripts, maps, rare books, musical scores, recordings, films, prints, and photographs. By evaluating these aspects, the study aims to highlight the role of WDL in global digital preservation, its strengths, limitations, and areas for potential enhancement.